Economic And Asymmetric Information As Moderation Variables, Credit Risk And Credit Prices - Suyanto; Zaharuddin; Masno Marjohan; Jeni Andriani (Jurnal Manajemen, 2024)
Profitability denotes a company's capacity to generate earnings within a specified timeframe. Companies that thrive and exhibit profitability are perceived as successful and typically garner favour among shareholders. This study examines profitability in the context of a company's ability to generate earnings within a specified timeframe, which is crucial for shareholder favour and business success. It focuses on the banking sector in Indonesia, encompassing 33 listed entities, with eight selected for the research sample. Employing hypothesis testing and analytical techniques, the study finds that asymmetric information and fluctuations in profitability do not affect credit pricing. Instead, credit risk positively impacts credit pricing, along with positive contributions from asymmetric information and profitability. This suggests that profitability does not hinder creditworthiness improvements. Asymmetric information does not affect credit pricing, making selling bank loans risky. Further research on credit pricing at a larger scale is warranted.